The synergies of University Education and Primary health Care to meet populations health needs - Blandi, L.; Odone, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
In the last decades, the World Health Organization has sensitized all countries to adopt a Primary Health Care approach in their health systems. It is also important to invest in education about primary health care. Indeed, we need to spread this comprehensive culture of health, starting from university education, and continuing during the whole work-life cycle. Due the current medical model, approaching patient by specific pathology or discipline, inefficiencies have been generated due to a lack of communication and integrated management of chronicity. Public Health can build dynamic models and mechanisms that pursue the health needs expressed by populations and education plays a crucial role in enhancing a country’s resilience and protecting the health of its inhabitants. All the health workers should consider all the aspects of health, beyond the specific phases of diagnosis and treatment. Continuous education and training are key elements to focus on, to satisfy our population’s health needs.